A Cross-Country Nonparametric Analysis of Bahrain's Banking System - Manole, Vlad (IMF Working Papers; Working Paper ;, 2005)
Bahrain's financial sector development strategy succeeded in building a leading regional banking center, which has become one of the main engines of growth and sources of employment. Although the simulations conducted in the paper suggest that the banking sector in Bahrain continues to occupy a front-runner position among those in a sample of member countries of the Gulf Cooperation Council, they also reveal that: (i) as expected, banks in Bahrain still lag behind their Singaporean counterparts, and (ii) there is strong competition from other countries in the region. The paper also finds that in terms of scale efficiency, the banks in Bahrain operate at the same level as banks in Singapore and their closest competitors in Qatar and the United Arab Emirates. The results appear to be robust with respect to changes in the sample size and model specifications.